Improving Financial Literacy and Entrepreneurial Spirit for Indonesian Migrant Workers - Raharjo, Tri Joko; Harianingsih, Harianingsih; Sumartiningsih, Sri; Mu’arifuddin, Mu’arifuddin (Journal of Community Empowerment, 2024)
Community service was carried out to improve financial literacy and entrepreneurial spirit in participants, namely Indonesian migrant workers in Taiwan. The implementation of this activity was attended by 20 participants and took place at the Indonesian Trade and Economic Office in Taipei, Taiwan. The problem experienced by partners was the lack of ability to plan finances while working as Indonesian workers in Taiwan, so that when they retire there was no business or business to manage. Usually Indonesian migrant workers send income while in Taiwan to their families in Indonesia as daily living expenses and to build a house. The program methods used in this activity include partner observation, preparation, training and evaluation. During the implementation, a questionnaire was distributed in the form of a google form. The results of the activity showed that there was an increase in knowledge about financial management for Indonesian migrant workers reaching 85%, an increase in skills in making entrepreneurial plans by 80% and motivation to become entrepreneurs after returning from Taiwan by 95%.